Nilai-Nilai Pendidikan Karakter dalam Gending Rare sebagai Upaya Melestarikan Kearifan Lokal Bali - Ida Bagus Brata (Diakronika, 2019)
This study aims to find out the values ​​of character education that can be transferred through gending rare to early childhood as an effort to preserve Bali local wisdom. The present study concerns on: what values ​​of character can be educated through gending rare in an effort to preserve Bali local wisdom; part of character education values in gending rare that can be carried out in an effort to preserve local wisdom; when will the value of character education in gending rare as an effort to preserve local wisdom be carried out; how gending rare rhythms can instill character education as an effort to preserve local wisdom in early childhood. This study uses a qualitative descriptive method. The results showed that the value of character education that can be educated through gending rare can be of individual and social dimensions. The value of individual character education, such as religious, hard work, independence, responsibility, tough, humble, honesty, helpful, and cheerful. While those that are social, such as love the homeland, care for the environment, and togetherness. These character values ​​are part of the universal value of local wisdom that is important to be instilled in the process of forming children's personality from an early age. The value of character education in gending rare can be done at home, at school, and in the community; when parents bathe the child, when the child is fed, when sleeping the child, when playing with peers, with caregivers or with their parents. It generally sung by parents with melodious rhythms and with joyful rhythms.